Justiça do trabalho : demandas trabalhistas no Norte do Rio Grande do Sul (1941-1960) - Luz, Alex Faverzani da (2011)
Program hopes to address through this research, the emergence and historical development of the Labour Court as a milestone in the conquest of labor and social rights of the working class in Brazil. The advent of the Labour Court came as a result of evolutionary steps in social struggles, in order to ensure dignity and justice for workers, backed by labor rights, founded along the Constitutional enactments and the Consolidation of Labor Laws of 1943. Thus, the aim is to list the main steps of this path which, little by little, shaped and perfected the Labour Court in Brazil, as well as further research along the historic city of Passo Fundo, especially in the period that concerns the installation of the Labour Court in the county in 1959. Thus, the research will timeframe the period 1941 to 1960, and March as the regional city of Passo Fundo, RGS, Brazil. Still, the research will conduct analysis of judgments of labor from 1959 to 1960, with the aim of developing historical research together with the documentary sources that illustrate the evolution of the Labour Court as a member institution of the Judiciary. Through this documentary research will be possible to map relevant data such as the professional profile that litigated in the Labor Court of Passo Fundo, claims postulates more frequently, and the decisions that were handed down by magistrates degree of judgment